Investigation the Impact of Deforestation on Historical & Archaeological Resources (The Case Study of Wilpattu National Park, Sri Lanka) - Nimalasiri, L.K.D.C.H.; Wickramasinghe, W.M.P.W. (University of Jaffna, 2018)
- The Wilpattu National Park (WNP) is the oldest and largest National Park of the country, Sri Lanka. It has 60 lakes and tanks spread across 131, 693.7 hectares in the Northwest coast lowland dry zone in Sri Lanka (Jayawardana, 2015). In 1905 the area was designated a sanctuary and in 1938 it was upgraded to the National Park status (Hettiarachchi, 2010). Archaeologically important sites at WNP can be divided into five major categories based on the artifacts (IUCN, 2006). The overall aim of this study was to identify the devastation of archaeological resources due to the deforestation at WNP. Specific objectives were to find out the present situation at WNP, identify the resettlements and new constructions, which conducted at WNP and to identify the existing management system. In order to achieve the objectives of this study, the required data were collected both from primary and secondary sources. The study found that the threat of WNP and the surrounding region mostly for archaeological resources first arose in 2009. This was due to the construction of two illegal roads. A 50-acre section of forestland that had been destroyed come under the Wilpattu North Sanctuary (WNS). Moreover, there is an important archaeological site at WNS, with artifacts dating back to the time of the Mohenjo-daro civilization. Human settlement of the WNP poses a direct threat to the conservation of all vital archaeological resources. To conserve these vital resources researcher identified that Consulting Environmental Organizations, Civil Society Organizations, Archaeological departments and coordinating a joint effort to mitigate the damage is a must. Archaeological Impact Assessment (AIA) procedures should compulsory for any settlements, which, are conducted at archaeologically important places. The surface recognition study was carried out to record the archaeological sites and their present status.
Keywords: Archaeological resources; Deforestation; Devastation; Sanctuary